Neotrombicula gamaensis Yang 1985 ... - Ma, Min; Li, Sheng-Cai; Fan, Qing-Hai (Zenodo, 2015)
182. Neotrombicula gamaensis Yang, 1985 Host/Habitat. Microtus oeconomus (tundra vole), rodents. Distribution. Jiangxian, Yicheng (Zhang et al. 1999). ... : Published as part of Ma, Min, Li, Sheng-Cai & Fan, Qing-Hai, 2015, Mites and ticks (Acari) in Shanxi Province, China: an annotated checklist, pp. 1-39 in Zootaxa 4006 (1) on page 29, DOI: 10.11646/zootaxa.4006.1.1, http://zenodo.org/record/289262 ...